CLIMATE CHANGE AND GREEN FISCAL POLICY: A SYSTEMATIC LITERATURE REVIEW ON ENVIRONMENTAL TAXATION AND SUSTAINABLE ECONOMIC GROWTH - Mas Ning Zahroh (Jurnal Ekonomi dan Manajemen, 2025)
This paper presents a systematic literature review on the intersection between climate change mitigation and green fiscal policy, with a specific focus on environmental taxation and its role in promoting sustainable economic growth. In response to the escalating climate crisis, governments worldwide are adopting fiscal instruments such as carbon taxes, pollution levies, and green subsidies to internalize environmental externalities and shift market behavior. This review synthesizes findings from 40 peer-reviewed articles and policy reports published between 2010 and 2024, examining both theoretical and empirical perspectives. The review identifies three major themes: (1) the effectiveness of carbon pricing in reducing emissions, (2) the role of fiscal incentives in accelerating green technology adoption, and (3) the distributional impacts and political economy challenges of implementing green tax reforms. Results show that while carbon taxation can reduce emissions by up to 20% in certain jurisdictions, its success is highly context-dependent, shaped by institutional strength, public trust, and economic structure. The study concludes that green fiscal policy is a powerful but complex tool that requires careful design to balance environmental goals with equity and economic competitiveness. It also highlights research gaps, particularly in low-income countries, and calls for more interdisciplinary approaches in evaluating long-term outcomes. This review contributes to the growing discourse on climate-responsive public finance and provides policy insights for designing effective, equitable, and growth-oriented environmental tax regimes.